Formation of Creative Thinking of Students of a Pedagogical University by Means Of Information Technology In Learning Mathematical Disciplines - Sodikova, Makhmudova D.M.; Dusmurodova G.H., Sh.M. (International Journal of Psychosocial Rehabilitation, 2020)
This article was written with the aim of creating creative thinking of students of a pedagogical university by means of information technology in the teaching of mathematical disciplines. The following tasks are ahead of the article as: on the basis of the analysis of new pedagogical, psychological and methodological literature to determine the main parameters and criteria of students’ creative thinking; to analyze the content and identify the importance of mathematical and methodological disciplines in the vocational training of students of the specialty "Pedagogy and methodology of primary education"; determine the totality of tools and techniques necessary for the formation of creative thinking of a future teacher; to identify the psychological and pedagogical conditions for the successful formation of creative thinking of students by means of mathematical disciplines; to develop and implement an educational and methodological complex for the formation of creative thinking of students - future primary school teachers using information and communication technologies.